FORMULASI SEDIAAN BLUSH ON DARI EKSTRAK KUBIS UNGU (Brassica Oleracea L. var. capitates f. rubra) SEBAGAI PEWARNA DALAM BENTUK COMPACT POWDER - Nadia Nadia (Jurnal Penelitian Farmasi & Herbal, 2022)
Cosmetics have been known to humans since centuries ago. Since the last 40 years, cosmetics has grown rapidly. Quantias and the quality of biological materials for use on the skin are increasing. Blush on is created from attractive colors and of course using coloring agents. Purple cabbage extract is used as a dye in blush on with a concentration of 30% and Isopropyl myristate as a binder with various concentrations of 0.5%, 1.0% and 2.0%. Purple cabbage extract was obtained by 96% ethanol maceration, then filtered and rotary using a rotary evaporator, then evaporated in a water bath with a temperature of 700 C. Blush on is made by pressing. The extract yield obtained was 18.68%. The observations show that preparations with a concentration of Isopropyl myristate 1.0% are better and more preferable because the preparation is not brittle and not too hard. In the pH test, all dosages meet the requirements. In the irritation test, all preparations did not cause irritation reactions to all panelists. Purple cabbage extract can be used as a natural dye in the process of making blush on and the best concentration of Isopropyl myristate is 1.0%.